Inkdeath [compact disc, unabridged] - Funke, Cornelia, 1958- (Listening Library, 2008)
The Inkworld trilogy ends with a bang! With the Book of Immortality coming apart, the Adderhead finds himself vulnerable. He sentences the kingdom's children to toil in the silver mines until Mo agrees to fix the Book.